Suomen EU-jäsenyyden vaikutukset tuottajien ja kuluttajien hyvinvointiin - Penttilä, Anne (Maatalouden taloudellinen tutkimuslaitos, 1997)
Tutkimuksessa tarkastellaan Suomen EU-jäsenyyden hyvinvointivaikutuksia tuottajien ja kuluttajien hyvinvointiin kahden ensimmäisen jäsenyysvuoden aikana. Taloudellisilla ylijäämäkäsitteillä, eli tuottajan ja kuluttajan ylijäämillä, voidaan määrittää, kuinka paljon kumpikin ryhmä on markkamääräisesti jäsenyyden seurauksena hyötynyt tai hävinnyt. Tutkimuksessä käytettiin maatalouden simulaatiomallia, jossa verrattiin kahta eri skenaariota. Toisen skenaarion mukaan Suomi olisi jatkanut kansallisen maatalouspolitiikkansa harjoittamista vuoden 1994 mukaisesti EU:n ulkopuolella. Toinen skenaario kuvaa vuoden 1996 toteutunutta tilannetta, jossa Suomi on EU:n jäsen. Suomen EU-jäsenyyden seurauksena maataloustuottajat kärsivät hyvinvointitappiota kun taas elintarvikkeiden kuluttajat saivat hyvinvointivoittoa. Suurimmat tappiot tuottajille koituivat maidon tuotannosta, mutta myös naudan- ja sianlihan tuotannon tappiot olivat merkittäviä. Kuluttajien hyvinvointivoitto oli seurausta lähinnä sian- ja naudanlihan hintojen laskusta.

The aim of this study was to evaluate how the EU membership has affected the Finnish agricultural sector and, consequently, consumers and farmers welfare. The effects were studied using the common welfare measures, producer surplus and consumer surplus. The producer and consumer surpluses were estimated by an agricultural simulation model developed in Germany. The model requires two kinds of main inputs, statistical information about prices and quantities, and calculations of production-specific support paid in 1994 and 1996. The base scenario for 1996 was built by recreating the situation of 1994, adjusting only for the changes due to consumption trends and productivity increases. This base scenario describes the situation where Finland remains outside the EU and continues its own agricultural policy. The base scenario was then compared to the so-called EU scenario, in which prices and support measures amount to the actual ones paid in 1996. The volumes of production and supply were also approximately calibrated to the actual volumes of 1996. The starting point of the model was to estimate the production and consumption. This was done by utilizing the Cobb-Douglas supply and demand functions. On the basis of the estimation results from the base scenario and the EU scenario, the welfare changes of the producers and consumers were determined. The changes in the set-aside system were not included in the model and, therefore, the effects of the crop production could not be clearly determined. Thus, the main focus was on animal husbandry. According to the study, the farmers welfare loss due to the EU membership was FIM 3.3 billion. If results from crop production are also accounted for, the loss was about FIM 4.0 billion. The biggest losses resulted from milk production, but the losses in beef and pork production were also significant. According to the study, consumers have gained FIM 1.1 billion, and the share of the animal production was FIM 0.7 billion of this. The consumers welfare gain was mainly a result of the decline in pork and beef prices. To study the welfare change in the whole society, the welfare change of the taxpayers was evaluated by comparing the subsidies paid to the agricultural sector in 1994 and 1996. As a result of the decrease in the subsidies paid by the government, the taxpayers welfare gain was FIM 2.1 billion. According to the study, the net welfare change in Finland, in terms of the agricultural sector only, was a welfare loss of FIM 0.8 billion.
Effects of the EU membership on the welfare of producers and consumers in Finland
Raportti perustuu pro gradu -tutkielmaan, jossa tarkastellaan integraation hyvinvointivaikutuksi ex post eli tapahtuneeseen kehitykseen perustuen. Tarkastelujakso on vuodesta 1994 vuoteen 1996.
Keywords: Ma; EU-jäsenyys; tuotanto; kulutus; hyvinvointi; maataloustuet; EU membership; production; consumption; welfare; support